Fat embolism syndrome in a child with sickle cell disease - Sohini Chakraborty; Arun Danewa; Sunisha Arora; Saurabh Bansal; Parminder Pal Singh; Rahul Bhargava; Vikas Dua (Elsevier, 2024)
Background: Fat embolism syndrome (FES) is a rare and underdiagnosed complication associated with sickle cell disease. Case report: We report the case of a 12-year-old girl with sickle cell disease who initially presented with features of acute vaso-occlusive crisis. However, she later developed neurological and respiratory complications along with a decrease in hemoglobin and platelet counts. She was evaluated and diagnosed with FES. The patient was successfully managed with red cell exchange and therapeutic plasma exchange, leading to complete recovery. Conclusion: Prompt diagnosis and early management can significantly improve the outcome of this rare, though highly morbid complication.